Latecomers - Douglas, C (Enigma, 2007)
Authorship and authority, originality and influence are genealogical concerns, arising in the relationship between a maker and his or her precursors. Influence is traditionally understood as the extent to which one’s work is attributable to another. There is a common critical mode in which influence is employed as a mechanism to establish inter-generational debt. This paper is written against this type of economic analysis. Instead, it presents a criticism which describes genealogy as actively antagonistic, rather than as a process of passive inheritance. Two theorists who discuss the anxiety of being a latecomer are presented: Harold Bloom, who writes of the poetry as constituted in the struggle of a latecomer with his or her significant precursors; and Sir Thomas Browne, who describes the anxiety of inhabiting a degenerating world. Both theorists describe the need for the latecomer to clear a space (literal or figurative) in which to work. Two architectural relationships are offered as examples of this anxiety, and this need to clear space. The relationship between Adolf Loos and K. F. Schinkel is shown to be not quite how Loos describes it; and the Roman Emperors Hadrian and Augustus are shown to contend for authority in the construction of their respective mausolea.
Keywords: Architecture; Authorship; Influence; Genius; Harold Bloom; Adolf Loos; Karl Friedrich Schinkel; Thomas Browne